The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/dom.14060
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy and safety of dapagliflozin in patients with inadequately controlled type 1 diabetes (the DEPICT‐2 study): 52‐week results from a randomized controlled trial

Abstract: Aim To investigate the long‐term efficacy and safety of dapagliflozin as an adjunct to adjustable insulin in adults with type 1 diabetes (T1D) and inadequate glycaemic control. Materials and Methods Dapagliflozin Evaluation in Patients with Inadequately Controlled Type 1 Diabetes (DEPICT‐2) was a placebo‐controlled, double‐blind, multicentre, phase III study of adults with T1D (HbA1c 7.5%‐10.5%) randomized (1:1:1) to receive dapagliflozin 5, 10 mg, or placebo. The effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 28 publications
4
61
1
Order By: Relevance
“…Weight reduction was seen in patients as shown in Table 2. The most significant finding was a decrease of up to 5% as compared to placebo [18]. Weight loss can be attributed to the loss of calories in the urine.…”
Section: Non-glycemic Benefits Of Sglt2 Inhibitorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Weight reduction was seen in patients as shown in Table 2. The most significant finding was a decrease of up to 5% as compared to placebo [18]. Weight loss can be attributed to the loss of calories in the urine.…”
Section: Non-glycemic Benefits Of Sglt2 Inhibitorsmentioning
confidence: 94%
“…Only, two studies mentioned changes in blood pressure. A meta-analysis of sotagliflozin [17] mentioned a 4mm Hg drop, while the DEPICT-II trial observed an average 3mm Hg reduction with 5mg and 7mm Hg with 10mg dapagliflozin [18].…”
Section: Non-glycemic Benefits Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…DEPICT-2 was the second of two, randomized, doubleblinded, placebo-controlled, 52-week phase 3, multicenter clinical trials providing further supportive evidence for the use of dapagliflozin as an adjunct therapy in T1D. 70 The study design being similar to DEPICT-1, participants were from different geographical regions, the DEPICT-1 trial having majority subjects of European descent but DEPICT-2 trial having~20% from the Asia-Pacific region. At 52 weeks, dapagliflozin 5 and 10 mg were associated with a significant reduction in HbA1c .…”
Section: Sglt1 and Sglt2 Inhibitorsmentioning
confidence: 99%
“…Additionally, these agents reduce the magnitude of postprandial glucose excursions and increase glucose time-in-range (BG 70-180 mg/dL) as supported by the CGM data. [69][70][71]74 Improved glycemic control is accompanied by a meaningful (3%-5% of bodyweight from baseline) and sustained weight loss with these agents, which is due to fat reduction related to caloric loss from increased glycosuria. The beneficial effect of SGLT1/SGLT2 inhibitors on weight may help to rectify the negative effect of weight gain associated with intensive insulin treatment on cardiovascular risk profile.…”
Section: Sglt1 and Sglt2 Inhibitorsmentioning
confidence: 99%
“…Combined, 813 patients with inadequately controlled T1DM were studied. [17][18][19][20][21] HbA1c decreased significantly with both doses of dapagliflozin up to 52 weeks (Table 1). There was an improvement in TIR of approximately 10% (9.02% for dapaglilozin 5 mg and 10.70% for dapagliflozin 10 mg), which meant that patient's glucose levels were within the target zone for an extra 2 h a day (p < 0.0001) ( Table 1).…”
Section: Introductionmentioning
confidence: 97%